PCM: maintenance planning and control - Sanitá, Willian Matheus; Campos, Ronaldo Ribeiro de (Revista Interface Tecnológica, 2020)
The emergence of machines and the advent of industrialization brought with it the maintenance process, an important factor with a great impact on the costs and profits of any company. Investing in maintenance planning is an important strategy to bring improvements and often guarantee the quality of products, which is essential in a highly competitive market, which seeks at all costs to meet the needs of its customers, who are increasingly demanding. Within this context, Maintenance Planning and Control (PCM) has an important role within organizations. The purpose of this study is to highlight the importance of PCM and maintenance management, as a basis for improving failures and contributing to the company’s growth. The methodology used in this study was a literature review, with website consultations, articles, books, theses and dissertations that have PCM and its applicability as its main subject. The studied literature brings the benefits of PCM and how its implementation can bring positive results for companies.